Astronomically forced variations in western African rainfall (21°N-20°S) during the Last Interglacial period - (:unkn) unknown (My University, 2014)
This study documents the long-term evolution of western African precipitation during the Last Interglacial (LIG). We compare geochemical records obtained on nine sediment cores from the western African margin to a transient simulation (130-115 ka) performed with an ocean-atmosphere general circulation model and insolation as sole forcing. Good agreement between proxy records and model outputs indicates that long-term changes in western African precipitation largely responded to insolation variations during most of the LIG. After an early LIG dry phase (related to high-latitude iceberg melting or dating uncertainties), boreal summer insolation controlled the intensification of the North African monsoon between 127 and 122 ka, perhaps facilitating human migrations out of Africa. Equatorial African rainfall slightly increased throughout the LIG in response to increasing annual insolation. East-west contrasting rainfall evolutions at 10-20°S illustrate the complex southern African response, in contrast to more direct responses of North and equatorial western Africa, to insolation forcing.
Keywords: African Research